Customer Satisfaction as a Key Driver of M-Tix Usage Intention: An Analytical Study - Stefania, Fellencia (International Ecsis Association, 2024)
Increasingly developing technology has given rise to various innovations, online tickets have been adopted by several well-known cinemas, one of which is Cinema XXI's M-Tix. This research aims to see satisfaction and intention in using M-Tix among the public by knowing the influence of promos and service costs, customer trust and M-Tix display design. This research used data from 101 respondents with an age range of 15-30 years. This research analysis uses Path Analysis (a combination of multiple regression and mediation models). The research results showed that promos and service costs had a negatif effect on customer satisfaction. Meanwhile, customer trust and M-Tix appearance design. Customer trust and M-Tix display design have a positive effect on customer satisfaction. The M-Tix display design has a positive effect on customer usage intention through the customer satisfaction variabel. The implication of the paper is that M-Tix must carefully evaluate and optimize their promotional offers, discounts, and service fees to align with customer expectations, while concurrently fostering trust and enhancing user interface design to significantly boost customer satisfaction and usage intention.